L’esperienza raddoppiata. L’individuazione della memoria nell’era della transizione digitale - Cangialosi, Riccardo (Mechane, 2022)
This contribution aims to reflect about the question of technology in Bernard Stiegler’s thought starting from a consideration about the original concepts of this branch in the twentieth-century philosophical thought with Gilbert Simondon and Martin Heidegger as founding fathers. A reflection halfway between metaphysics and politics to rethink the conditions of current state of existence and the possibilities in the future of overthrowing the hyper-industrial capitalist society.